Frostbite protection in mice expressing an antifreeze glycoprotein. - Martin Heisig; Sarah Mattessich; Alison Rembisz; Ali Acar; Martin Shapiro; Carmen J Booth; Girish Neelakanta; Erol Fikrig (PLoS ONE, 2015)
Ectotherms in northern latitudes are seasonally exposed to cold temperatures. To improve survival under cold stress, they use diverse mechanisms to increase temperature resistance and prevent tissue damage. The accumulation of anti-freeze proteins that improve cold hardiness occurs in diverse species including plants, arthropods, fish, and amphibians. We previously identified an Ixodes scapularis anti-freeze glycoprotein, named IAFGP, and demonstrated its cold protective function in the natural tick host and in a transgenic Drosophila model. Here we show, in a transgenic mouse model expressing an anti-freeze glycoprotein, that IAFGP protects mammalian cells and mice from cold shock and frostbite respectively. Transgenic skin samples showed reduced cell death upon cold storage ex vivo and transgenic mice demonstrated increased resistance to frostbite injury in vivo. IAFGP actively protects mammalian tissue from freezing, suggesting its application for the prevention of frostbite, and other diseases associated with cold exposure.